WRF Model Simulation of the Active and Break Spells of Summer Monsoon over Bangladesh during 2011 and 2013 - Ferdoushi, Zannatul; Quadir, DA; Das, Someshwar; Panda, Subrat Kumer; Hassan, SM Quamrul (The Dhaka University Journal of Earth and Environmental Sciences, 2023)
In this paper, the weather systems associated with the active and break spells of summer monsoon over Bangladesh have been studied using the WRF model as a regional climate model for two selected years 2011 (excess rainfall year) and 2013 (deficit rainfall year). The active and break spells for two selected years were identified using daily observed rainfall data from Bangladesh Meteorological Department (BMD). The model simulations for each year were made for the period of 1st May to 30th September with a single domain of 30 km resolution and 19 vertical levels. FNL 1°×1° resolution data was used for model simulation. The model-simulated daily rainfall, Sea Level Pressure (SLP), and the wind at 850 hPa, and 200 hPa were compared with TRMM, and ERA-Interim data, respectively. This study reveals that the increase in rainfall is concurrent with a south-westerly wind and the decrease of rainfall simultaneously occurs with a south-easterly wind over the country. A cyclonic circulation (850 hPa) was found over the southwestern part of Bangladesh during active days and the south-easterly wind was found (850 hPa) during break days. The easterly wind was found (200 hPa) during active days and break days. The lowest SLP was found over the southern part during active days (992-995 hPa) compared to break days (998-100 8hPa). Outgoing Longwave Radiation was found high (250-275 W/m²) during break days compared to Active days (220-270 W/m²). The WRF model can reasonably capture well the active and break phases of summer monsoon for the years 2011 and 2013. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 11(2), 2022: P 43-52